Arcs of communication and small- and medium-sized enterprise performance. Issue 4 (23rd October 2019) - Yanes-Estévez, Vanessa; García-Pérez, Ana María; Oreja-Rodríguez, Juan Ramón
Abstract : Purpose: The purpose of this paper is to analyse the information shared by SMEs with their main customers and suppliers and its implications on their performance. Design/methodology/approach: The paper puts forward the concept of arcs of communication based on the frequency and direction of the information exchanged by SMEs with their main customers and suppliers. SMEs are classified by the arc of communication they belong to using data from a survey carried out in the Canary Islands (Spain). The Rasch Measurement Theory is applied. Findings: The largest group of small- and medium-sized enterprises (SMEs) shares information frequently with both customers and suppliers (broad arc of communication). Differences were detected in the performance of SMEs belonging to this broad arc, as well as, in those firms that communicated frequently with their main suppliers (asymmetrical arc of communication towards suppliers). In both cases, these firms were better than their competitors in innovation. Practical implications: This study demonstrates the need for better management of the links between SMEs and their suppliers and with their customers in accordance with their strategies, promoting a greater cooperative behaviour throughout the supply chain. Originality/value: SMEs' customers and suppliers are their main sources of information compared to large firms, which have greater resources to search for and acquire information. This paper investigates the information exchanged by SMEs with their main customers and suppliers from a strategic focus by adding to the literature the concept of arcs of communication. It also has the added value of applying the Rasch Measurement Theory (Rasch, 1960/1980).